2020
DOI: 10.1101/2020.04.10.036442
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-molecule diffusometry reveals no catalysis-induced diffusion enhancement of alkaline phosphatase as proposed by FCS experiments

Abstract: Theoretical and experimental observations that catalysis enhances the diffusion of enzymes have generated exciting implications about nanoscale energy flow, molecular chemotaxis and selfpowered nanomachines. However, contradictory claims on the origin, magnitude, and consequence of this phenomenon continue to arise. Experimental observations of catalysisenhanced enzyme diffusion, to date, have relied almost exclusively on fluorescence correlation spectroscopy (FCS), a technique that provides only indirect, ens… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…One notable case is the enzyme alkaline phosphate, which catalyzes a highly exothermic reaction with H =−43.5 kJmol -1 yet positive G = +30.2 (28) or +61.5 (29) kJmol -1 at a high turnover rate. This shows no detected enhanced diffusion in our study, in agreement with a recent earlier study (21). Therefore, we consider it more meaningful physically to seek correlation with G, the maximum available work that can be extracted from the reaction (15,16).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…One notable case is the enzyme alkaline phosphate, which catalyzes a highly exothermic reaction with H =−43.5 kJmol -1 yet positive G = +30.2 (28) or +61.5 (29) kJmol -1 at a high turnover rate. This shows no detected enhanced diffusion in our study, in agreement with a recent earlier study (21). Therefore, we consider it more meaningful physically to seek correlation with G, the maximum available work that can be extracted from the reaction (15,16).…”
Section: Resultssupporting
confidence: 93%
“…The other enzymes -aldolase, phosphoglucoisomerase, pyruvate kinase, hexokinase, and phosphofructokinase, were selected from the glucose cascade cycle (25). Among the three endergonic reactions (G > 0), alkaline phosphatase and triosephosphate isomerase were selected to repeat the measurements of an earlier study (14,21), and phosphoglycerate kinase was selected from the glucose cascade cycle. The substrate concentrations were selected to give reaction half-lives of a few minutes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientists have developed new types of single-molecule traps aiming to overcome such shortcomings. For example, the anti-Brownian electro-kinetic (ABEL) trap 1,2 can hold a dye-labeled protein for seconds using real-time electro-kinetic feedback control. Electrostatic fluidic traps were shown to trap unfolded dye-labeled proteins under very low salt conditions, and to detect their charge 3 .…”
mentioning
confidence: 99%
“…It has been suggested that experimental artifacts affecting FCS may be responsible for the high diffusion coefficient values reported in the literature (Günther et al , 2018; Feng & Gilson, 2019). Along these lines, alternative techniques such as nuclear magnetic resonance (Günther et al , 2019), dynamic light scattering (Zhang et al , 2018), anti‐Brownian electrokinetic trapping (Chen et al , 2020), and single‐molecule displacement mapping (Choi et al , 2022) have found no diffusion enhancement for some of these enzymes, namely, aldolase and alkaline phosphatase (Riedel et al , 2015; Illien et al , 2017). Nevertheless, other techniques, such as single‐molecule measurements using total internal reflection fluorescence microscopy, have reported an even higher diffusion coefficient for urease than the value obtained with FCS (Xu et al , 2019).…”
Section: How Could Enzymes Perform Work During Catalysis?mentioning
confidence: 99%